2011
DOI: 10.1007/s00216-011-4844-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a LIBS assay for the detection of Salmonella enterica serovar Typhimurium from food

Abstract: Laser-induced breakdown spectroscopy (LIBS) is used for the identification of the presence of hazardous bacteria in food. In this study, our main focus was centered on the identification of S. enterica serovar Typhimurium, a Gram-negative foodborne pathogen, in various liquids such as milk, chicken broth, and brain heart infusion due to the infection being most prevalent in raw meat and dairy products. A Nd:YAG laser of operating wavelength 266 nm was used to obtain the spectra from the artificially inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This study showed a saturation or flattening out of the response curve at concentrations above 10 11 CFU/mL. Barnett et al tested concentrations of S. enterica that spanned eight decades (10 1 to 10 8 CFU/mL) as measured by DNA concentrations in the specimens prior to LIBS testing [77]. In blood-heart infusion, chicken broth, and milk, LIBS detection limits were 10 5 CFU/mL.…”
Section: Concentration/titermentioning
confidence: 92%
See 1 more Smart Citation
“…This study showed a saturation or flattening out of the response curve at concentrations above 10 11 CFU/mL. Barnett et al tested concentrations of S. enterica that spanned eight decades (10 1 to 10 8 CFU/mL) as measured by DNA concentrations in the specimens prior to LIBS testing [77]. In blood-heart infusion, chicken broth, and milk, LIBS detection limits were 10 5 CFU/mL.…”
Section: Concentration/titermentioning
confidence: 92%
“…Barnett et al studied the very important organisms Salmonella enterica (S. enterica) serovar Typhimurium, which is a Gram-negative foodborne pathogen responsible for salmonella [77]. Because this infection is most commonly caused by ingestion of raw meat or dairy products, the bacteria were inoculated into liquid samples of milk, chicken broth, and brain heart infusion.…”
Section: Food Contaminationmentioning
confidence: 99%
“…Ag and Au ions released into the media were measured using laser induced breakdown spectroscopy (LIBS). The measurement settings were a modification of Barnett et al (2011) . The excitation wavelength used was 266 nm and the laser energy was adjusted to 20 mJ.…”
Section: Methodsmentioning
confidence: 99%
“…In the food-preparation industry, the utility of using LIBS to rapidly identify bacteria responsible for foodborne contamination such as Salmonella enterica serovar Typhimurium [64] has been demonstrated. In the mining or environmental remediation industry, it has been shown that femtosecond LIBS can be used to discriminate inter-and intra-site differences in soil bacteria (at both the species and strain level) isolated from mining sites as an indicator of environmental soil quality [65].…”
Section: Libs Progress: 2005-2011mentioning
confidence: 99%